(untitled) (Journal of Applied Learning and Teaching, 2024)
Doctoral students are expected to conduct independent research and produce original contributions to their field of study. Therefore, doctorate programmes are rigorous and demanding, and they require a significant amount of dedication and hard work. High attrition and dropout rates generally mark the post-coursework phase of the programme because of the difficulties that go with the independent research aspect of the study. Supervisory practices are identified as major reasons for the discontinuance of these programmes. The purpose of this study was to identify the nature of communication on toxic supervision of PhD students by Twitter users. The data collection consisted of tweets posted between January 1, 2020, and March 12, 2023. The methodology used was content analysis, which included the examination of the tweets for themes and trends collected within the time frame. It provides valuable data on the lived experiences of PhD students under toxic academic supervision. This study reflects the value of Twitter as a tool for research and as a medium of expression and emotional support for PhD researchers. The study will contribute to policy-making and training in supervisory practices.